2016 IEEE 19th International Conference on Intelligent Transportation Systems (ITSC) 2016
DOI: 10.1109/itsc.2016.7795670
|View full text |Cite
|
Sign up to set email alerts
|

Driver identification using automobile sensor data from a single turn

Abstract: As automotive electronics continue to advance, cars are becoming more and more reliant on sensors to perform everyday driving operations. These sensors are omnipresent and help the car navigate, reduce accidents, and provide comfortable rides. However, they can also be used to learn about the drivers themselves. In this paper, we propose a method to predict, from sensor data collected at a single turn, the identity of a driver out of a given set of individuals. We cast the problem in terms of time series class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 18 publications
2
78
0
4
Order By: Relevance
“…Similar observations have been identified by other authors [8,16]. In [8], Hallac et al mention that as the driver pool increases, the alternative approaches using Multinomial Logistic Regression and Support Vector Machines "dropped off significantly" as compared to Random Forest. In [16] that Random Forest outperforms others for majority of assemblies.…”
Section: Classification For Driversupporting
confidence: 78%
See 1 more Smart Citation
“…Similar observations have been identified by other authors [8,16]. In [8], Hallac et al mention that as the driver pool increases, the alternative approaches using Multinomial Logistic Regression and Support Vector Machines "dropped off significantly" as compared to Random Forest. In [16] that Random Forest outperforms others for majority of assemblies.…”
Section: Classification For Driversupporting
confidence: 78%
“…Enev et al also hypothesized that given an availability of enough longitudinal data, "everyone can be distinguished." In another related work on driver identification, Hallac et al [8] demonstrated that there are unique patterns in individual driving styles which can be detected even for a short drive. Hallac et al experimentally demonstrated that the vehicle turn signature is often well suited for detecting individual style.…”
Section: Introductionmentioning
confidence: 99%
“…We achieve a mean accuracy of driver classification between 75-85% for CAN traces with a length of less than 2 minutes. By contrast, most prior works [3], [2] achieved comparable result only with fewer drivers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and when the exact signals could be extracted and are readily available for classification. • We propose a scalable technique to classify a large set of time series even if many of the individual time series are significantly noisy and hence lack sufficient predictive power individually.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, these methods are not well suited for IoT applications due to storage and transmission constraints [1], [2], whereas our lowdimensional embedding is compact, runs in real-time, and can aggregate data from many sensors and across many vehicles to continually improve its state estimator. Similarly, there has been work on driver identification [13], [30] and autolabeling of data [26], but these models are typically built for only one specific purpose. They are unable to transfer across different prediction types and thus struggle to extend into more general knowledge-based tasks.…”
Section: Introductionmentioning
confidence: 99%